Comparisons of In/Al doped ZnO on the density of states based on first-principles. (1st January 2013) - Zhao, Yanfang; Shang, Yuling; Li, Cailin; Gong, Jie; Yang, Ping
In order to obtain excellent optical and electrical properties of ZnO semiconductor light-emitting materials, some work has been done about the influence of doping. Models of pure ZnO, 12.5% Al-doped Zn0.875 Al0.125 O and 12.5% In-doped Zn0.875 In0.125 O are built respectively, and the electronic properties are calculated by first-principles method based on density functional theory (DFT). The results reveal that the lattice constants ( a, c ) of Zn0.875 In0.125 O are both larger than that of pure ZnO, which is in line with the changing of volume. The lattice constant a of Zn0.875 Al0.125 O is decreased while the c is amplified, and the volume of Zn0.875 Al0.125 O is reduced at the same time. The band gap of Zn0.875 In0.125 O is narrowed, while the band gap of Zn0.875 Al0.125 O is broadened. Moreover, through the analysis of density of states (DOS), we can know that the Al doping has a larger contribution to the electrical properties of ZnO than In doping. Al-3s and In-5s all have contributions to the total DOS at the CBM and Al-3p has an influence on the total DOS at the VBM, but In almost has no contribution to the total DOS. Based on the analysis above, it can be known that Al doping provides better electrical properties than In doping in getting promising n-type ZnO.